1993
DOI: 10.1007/bf02044229
|View full text |Cite
|
Sign up to set email alerts
|

Biomicroscopy versus fluorescein angiography of the iris in the detection of diabetic iridopathy

Abstract: Iris fluorescein angiography is not commonly employed in clinical practice, but it is the most sensitive technique for the evaluation of iris vessel abnormalities. We used iris fluorescein angiography as the gold standard against which to test the ability of iris biomicroscopy to demonstrate diabetic iridopathy (DI). One hundred and fourteen eyes of 63 diabetic patients affected by preproliferative or proliferative diabetic retinopathy (DR) (the DR groups at high risk of developing DI) were considered. The DI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…In case of doubt, examination of the anterior chamber angle and FAG of the iris vessels can help, as sensitivity and specificity of the latter are higher than those of biomicroscopy [50]. Iris angiography is also helpful when cataract or vitreous haemorrhage prevent retinal examination because, if iris new vessels are detected, PDR is highly likely to co-exist.…”
Section: Diagnosismentioning
confidence: 99%
“…In case of doubt, examination of the anterior chamber angle and FAG of the iris vessels can help, as sensitivity and specificity of the latter are higher than those of biomicroscopy [50]. Iris angiography is also helpful when cataract or vitreous haemorrhage prevent retinal examination because, if iris new vessels are detected, PDR is highly likely to co-exist.…”
Section: Diagnosismentioning
confidence: 99%
“…Mean intraocular pressure (IOP) was 31.8 ± 12.7 mmHg. The extent of iris neovascularization was graded using a scale ranging from 0−4, where 0 = no rubeotic iris vessels and 4 = maximal iris neovascularization (Bandello et al 1993). The mean grade of iris neovascularization was 2.5 ± 1.0.…”
mentioning
confidence: 99%
“…Some studies showed the occurrence of the capillary closure process in the macular region in NPDR too, with consequent foveal avascular zone enlargement.1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Although the number of cases affected by NPDR was restricted, we searched retrospectively for a correlation between evidence of quantitative or qualitative abnormalities of foveal avascular zone and iris hypoperfusion, without achieving a positive result. Therefore, capillary dilatations and iris hypoperfusion seem to be a manifestation of diabetic microangiopathy that are relatively independent from the severity of DR.…”
Section: Discussionmentioning
confidence: 99%